Serum calcium and incident diabetes: an observational study and meta-analysis. Issue 5 (May 2016) - Sing, C.; Cheng, V.; Ho, D.; Kung, A.; Cheung, B.; Wong, I.; Tan, K.; Salas-Salvadó, J.; Becerra-Tomas, N.; Cheung, C.
Abstract Summary The study aimed to prospectively evaluate if serum calcium is related to diabetes incidence in Hong Kong Chinese. The results showed that serum calcium has a significant association with increased risk of diabetes. The result of meta-analysis reinforced our findings. Introduction This study aimed to evaluate the association of serum calcium, including serum total calcium and albumin-corrected calcium, with incident diabetes in Hong Kong Chinese. Methods We conducted a retrospective cohort study in 6096 participants aged 20 or above and free of diabetes at baseline. Serum calcium was measured at baseline. Incident diabetes was determined from several electronic databases. We also searched relevant databases for studies on serum calcium and incident diabetes and conducted a meta-analysis using fixed-effect modeling. Results During 59, 130.9 person-years of follow-up, 631 participants developed diabetes. Serum total calcium and albumin-corrected calcium were associated with incident diabetes in the unadjusted model. After adjusting for demographic and clinical variables, the association remained significant only for serum total calcium (hazard ratio (HR), 1.32 (95 % confidence interval (CI), 1.02–1.70), highest vs. lowest quartile). In a meta-analysis of four studies including the current study, both serum total calcium (pooled risk ratio (RR), 1.38 (95 % CI, 1.15–1.65);I 2 = 5 %, comparing extreme quantiles) and albumin-corrected calcium (pooled RR, 1.29 (95 % CI, 1.03–1.61);I 2 = 0 %, comparing extreme quantiles) were associated with incident diabetes. Penalized regression splines showed that the association of incident diabetes with serum total calcium and albumin-correlated calcium was non-linear and linear, respectively. Conclusions Elevated serum calcium concentration is associated with incident diabetes. The mechanism underlying this association warrants further investigation.